The regulatory effect of sex steroids on the RhoA/ROCK pathway in the rat distal vagina. (12th January 2023) - Cellai, Ilaria; Comeglio, Paolo; Filippi, Sandra; Martinelli, Serena; Villanelli, Fabio; Amore, Francesca; Rapizzi, Elena; Maseroli, Elisa; Cipriani, Sarah; Raddi, Chiara; Guarnieri, Giulia; Sarchielli, Erica; et al.
Abstract: Background: Sex steroids have been demonstrated as important modulators of vaginal function. The RhoA/ROCK calcium-sensitizing pathway plays a role in genital smooth muscle contractile mechanism, but its regulation has never been elucidated. Aim: This study investigated the sex steroid regulation of the vaginal smooth muscle RhoA/ROCK pathway using a validated animal model. Methods: Ovariectomized (OVX) Sprague-Dawley rats were treated with 17β-estradiol (E2 ), testosterone (T), and T with letrozole (T + L) and compared with intact animals. Contractility studies were performed to test the effect of the ROCK inhibitor Y-27632 and the nitric oxide (NO) synthase inhibitor L-NAME. In vaginal tissues, ROCK1 immunolocalization was investigated; mRNA expression was analyzed by semiquantitative reverse transcriptase–polymerase chain reaction; and RhoA membrane translocation was evaluated by Western blot. Finally, rat vaginal smooth muscle cells (rvSMCs) were isolated from the distal vagina of intact and OVX animals, and quantification of the RhoA inhibitory protein RhoGDI was performed after stimulation with NO donor sodium nitroprusside, with or without administration of the soluble guanylate cyclase inhibitor ODQ or PRKG1 inhibitor KT5823. Outcomes: Androgens are critical in inhibiting the RhoA/ROCK pathway of the smooth muscle compartment in the distal vagina. Results: ROCK1 was immunolocalized in the smooth muscle bundles and blood vessel wall of the vagina, with weak positivity detected in the epithelium. Y-27632 induced a dose-dependent relaxation of noradrenaline precontracted vaginal strips, decreased by OVX and restored by E2, while T and T + L decreased it below the OVX level. In Western blot analysis, when compared with control, OVX significantly induced RhoA activation, as revealed by its membrane translocation, with T reverting it at a level significantly lower than in controls. This effect was not exerted by E2 . Abolishing NO formation via L-NAME increased Y-27632 responsiveness in the OVX + T group; L-NAME had partial effects in controls while not modulating Y-27632 responsiveness in the OVX and OVX + E2 groups. Finally, stimulation of rvSMCs from control animals with sodium nitroprusside significantly increased RhoGDI protein expression, counteracted by ODQ and partially by KT5823 incubation; no effect was observed in rvSMCs from OVX rats. Clinical Implications: Androgens, by inhibiting the RhoA/ROCK pathway, could positively contribute to vaginal smooth muscle relaxation, favoring sexual intercourse. Strengths and Limitations: This study describes the role of androgens in maintaining vaginal well-being. The absence of a sham-operated animal group and the use of the only intact animal as control represented a limitation to the study.